DAMPAK PSIKO-SOSIAL PADA MANTAN JUGUN IANFU - Trinovianto George Reinhard Hallatu (Universitas Musamus, Merauke, Papua, 2015)
ABSTRACTJapanese occupation in Indonesia which occurred in 1942-1945 had a huge impactfor the life ofthe Indonesian people. One of this impact is theexistence of comfort women, the indigenous woman whois forcedto serve thesexual needs of Japanese soldier and civilians. As a result ofsexual violence experienced by the former comfort womenin the past, bringing the min suffering both economically, psychologically and socially.This researchaimsto analyze thepsycho-social impactof one ofthe formercomfort womeninonevillageinSemarang. The method usedin this study isa qualitativecase studywithdata collection techniquessuch asobservation, interviewand literature study.The results show that the key informant, the former comfort women who became the object of this study suffered prolonged trauma and psychiatric disorders Post Traumatic Stress Disorder or PTSD. Former comfort women experiencing symptoms include repetition of the experience of trauma, avoidance and emotional numbing and increased sensitivity. In addition, the victim also suffered PTSD disorders include panic attacks, avoidance behavior, depressy, kill thoughts and feelings, and feel excluded and alone. But on the other hand the presence of the victim as former comfort women were not overly impact on social life. This is evident from the attitude of the local community who want to accept the existence of victims like ordinary community members and are not too concerned with the past that happened to the victim as former comfort women.